The importance of intracytoplasmic DPAS positivity in fine needle aspirates of breast lesions. Issue 2 (1st February 2001) - Johnson, S J; Wadehra, V
Abstract : Aims —For many years the presence of strong intracytoplasmic periodic acid Schiff (PAS) positive, diastase resistant (DPAS) staining within atypical cells has been used in this laboratory as a marker for carcinoma in fine needle aspirates from breast lesions. The aim of the current study was to document such DPAS positivity across the spectrum from benign to malignant breast disease and assess its value in the upgrading of cytology reports. Methods —Over a six month period, 315 aspirates were studied, each having sufficient cellular material for DPAS staining to be carried out on one whole slide. DPAS staining was recorded semiquantitatively as negative, equivocal, or positive (+, ++, or +++). The cytology results were correlated with any subsequent histology performed on these patients. Results —DPAS positive material was seen in both intracellular and extracellular locations. Care was needed in its interpretation. Occasional cells with apparently genuine intracytoplasmic positivity (+) were found in both benign and malignant cases. Frequent or particularly strong intracellular DPAS positivity (++, +++) correlated best with malignancy. Two cases were reliably upgraded from immediate reports suspicious of malignancy to final reports diagnostic of malignancy on the basis of the intracytoplasmic DPAS staining. Conclusion —Strict criteria are required for the interpretation of intracytoplasmic DPAS positivity and routine cytological appearances should also be taken into account. Weak positivity in occasional cells, especially in flat epithelial sheets, may be seen in benign lesions and is not reliable as a marker of malignancy. DPAS positivity with internal structure and producing nuclear indentation, especially in dissociated or atypical cells, correlates well with malignant histology and can be reassuring in the cytological diagnosis of malignancy.